1978
DOI: 10.3109/15563657808988233
|View full text |Cite
|
Sign up to set email alerts
|

Toxicologic Properties of Fluorescent Whitening Agents

Abstract: From the collection of toxicologic data, it is seen that the fluorescent whitening agents are a well-investigated class of compounds. Only in one of the groups of compounds investigated did it appear advisable to discontinue the use of a particular product on the basis of the toxicologic findings. In the large number of the other cases, the findings indicate that there is a considerable degree of toxicologic safety in the use of the FWAs in soap and detergent products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Although other investigations 2 have shown that certain individuals may be susceptible and develop skin sensitization to FWAs such as Uvitex, we had no evidence of such reactions occurring during our investigation. A prior positive skin patch test, conducted by a local physician, did not follow the protocol of the International Contact Dermatitis Research Group and therefore is difficult to interpret.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Although other investigations 2 have shown that certain individuals may be susceptible and develop skin sensitization to FWAs such as Uvitex, we had no evidence of such reactions occurring during our investigation. A prior positive skin patch test, conducted by a local physician, did not follow the protocol of the International Contact Dermatitis Research Group and therefore is difficult to interpret.…”
Section: Discussionmentioning
confidence: 49%
“…A very small number of cases had hypersensitivity, but no symptoms of manifest allergic or eczematous reactions were observed. 2 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In some toxicological experiments, the toxicity of some DSD‐FWAs was relatively low . However, in other studies, the 2S DSD‐FWA (C.I.85) could improve the peroral infection of the recombinant virus , and some FWAs affected the wound healing process . Moreover, the toxicity of many newly developed DSD‐FWAs and their photo‐isomers is still unknown.…”
Section: Introductionmentioning
confidence: 99%